Factors Affecting Smartphone Purchase Decisions of Consumers - Rai, Bharat; Dahal, Rewan Kumar; Ghimire, Binod (Management Dynamics, 2022)
This study aimed to pinpoint the factors influencing consumers' decisions to buy Smartphones in Kathmandu. The study examined how social factors, product attributes, and brand image affect consumers' decisions to buy Smartphones. The study focuses on the consumer's preferred method of choosing a Smartphone and which element influences that choice most. In the Kathmandu Valley, the demand for Smartphones is rising quickly. This study made use of primary data. The information was gathered from 394 buyers of cell phones in Kathmandu using a structured questionnaire and a convenient sampling technique. The elements influencing customer purchasing decisions for smartphones were found by using descriptive analysis, correlation analysis, and multiple regression analysis, which allowed for a good conclusion-drawing process. To investigate the Influence on purchasing decisions for Smartphones, product features, social factors, and brand image are used as independent variables. According to a correlation study, the dependent variable, consumer purchase decision in the purchase of a Smartphone, has a substantial association with all independent variables. The outcome of the regression analysis discovered that brand image, product attributes, and social factors significantly influence consumer purchasing behavior. The findings of the study are implacable for both the managerial level and the academic level. However, the study's findings can offer a researcher some theoretical direction. The results of this study may provide guidelines for formulating marketing strategies regarding Smartphones.